Importance of riding therapy in children with cerebral palsy in postural motor control - Costa, Thamara Cristhina Moreira da (2024)
Introduction: Cerebral palsy is a common neurological condition that affects the motor and cognitive development of children due to brain injuries occurring during the fetal, perinatal or postnatal period. It manifests itself as motor, postural and cognitive disorders, limiting the child's independence and autonomy. Given this reality, it is crucial to seek effective therapeutic interventions, capable of generating significant improvements in aspects of the pathology. There are positive results with the application of rehabilitation schemes designed to develop skills that allow them to better coordinate their motor activities. Gaining postural balance occurs through repetition, reaction and motivation, therefore, some therapeutic interventions have proven to be efficient in the rehabilitation of motor dysfunctions, and among them, equine therapy stands out. Equine therapy, a form of horse-assisted therapy, has emerged as an effective therapeutic intervention to improve postural motor control, balance and muscle strength. Objective: to analyze the importance of hippotherapy in postural motor control, and the benefits observed in postural motor development. Methodology: To conduct this research, the literature was analyzed about the impact of hippotherapy on postural motor control in children with cerebral palsy. Based on randomized controlled clinical studies, systematic reviews, magazines and articles in journals published between 2015 and 2024. The search was carried out in databases such as PubMed, SciELO, Google Scholar and VHL, using terms in Portuguese and English related to hippotherapy and cerebral palsy. Studies with patients diagnosed with cerebral palsy and undergoing hippotherapy were included. Results/Discussion: Equine therapy is an innovative therapeutic approach that uses horses as partners in the rehabilitation process of children with cerebral palsy. This practice offers significant physical benefits, improving postural motor control, balance, mobility and motor function. There are different types of hippotherapy, including passive hippotherapy, active hippotherapy and as a complete therapeutic technique. Physiotherapy plays a fundamental role in monitoring patients during equine therapy sessions. During the sessions, the horse's three-dimensional movement stimulates sensory and neuromuscular responses, promotes postural adjustments and improves motor coordination. Hippotherapy is also effective in regulating muscle tone and improving static and dynamic balance. Furthermore, the assessment of motor function using the GMFM-66 scale showed positive results. Finals Considerations: The study revealed that hippotherapy is effective in improving postural motor control in children with cerebral palsy. Furthermore, it brings important physical, emotional and psychological benefits, helping to regulate muscle tone, improve motor functions and neurological development. Interaction with the horse during hippotherapy sessions stimulates sensory and neuromuscular responses that contribute to these improvements. Thus, this research highlights the relevance of hippotherapy as a valuable therapeutic intervention for children with cerebral palsy, indicating the need for further studies to investigate its effectiveness in different types of this condition and analyze its long-term effects.